Influence of Yoga means on students’ biological age indicators - I.O. Sereda; G.Z. Lavrin; T.V. Kucher (Physical Education of Students)
Purpose: to determine effectiveness of Yoga means’ implementation in students’ physical education programs. Material: in experiment 85 2nd year students participated, who were divided in control group (CG, n=43, 15 boys and 28 girls) and experimental group (EG, n=42, 17 boys and 25 girls). Their calendar age was 18-19 years. By state of health all students were in main health group (without health problems). The researches were carried out during one academic semester and implied finding and comparing of students’ biological age. Results: by results of medical examination we registered 22 years as minimal biological age and 55 years as maximal. We found no students, whose biological age would correspond to calendar age. It was also found that systemic practicing of Yoga permits to keep proper level of students’ health and increase their interest to physical exercises’ practicing. It was proved that application of Yoga means approached students’ biological age to calendar one. Conclusions: introduction of Yoga complexes in physical education program will permit to sustain and improve students’ biological indicators and positively influence on their health.